(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In this study, we have studied the reduced differential transforms approach for nonlinear partial integrodifferential equations in which we discussed Strict and Non-Strict Inequalities, Existence Results, Maximal and Minimal Solutions, and then Comparison Theorems.